Equation A find the lowest number of the three. Equation A satisfies the given conditions.
<h3>What is even number? </h3>
If the number is divisible by 2 then the number will be an even number. Similarly, the number is not divisible by 2 then the number will be an odd number.
Assume the three consecutive integers are 2x,2x+2,2x+4
The sum of the three consecutive even numbers are 36;
x+x+2+x+4 = 36
3x+6=36
3x=30
x=10
The three integers are found as;
x =10
x+2 = 10+2 = 12
2x+4 =10+4=14
Hence, equation A find the lowest number of the three. Equation A satisfies the given conditions.
To learn more about the even number, refer to the link;
brainly.com/question/2289438
#SPJ1
Answer:
1 N 3
Step-by-step explanation:
25q + 10d = 425
q + d = 20
First thing's first, picture 4 quarters. Do you know how much these 4 quarters are worth? Obviously, you'd answer one dollar, but take the time to think about how exactly you came up with this answer.
"Well, it's simple," you might think, "Multiply 0.25 by 4."
Similar to this train of thought, the first equation is formulated by doing exactly that. 'q' represents an unknown number of quarters, and 'd' an unknown number of dimes. We use 25q and 10d, because, well, we're multiplying their value by the number of coins. They're equivalent to 425 because the 20 unknown coins make $4.25 (I converted it to cents to get rid of the pesky decimals, but if you want to keep it as dollars that works too).
Because the equation states that there are 20 coins in total, we know that we can make the equation 'q + d = 20' since there are 20 quarters and dimes in total.
Let me know if you need any further explanation :)
-T.B.
Answer:
x = 5
Step-by-step explanation:
The difference between consecutive terms will be equal , then
a₂ - a₁ = a₃ - a₂ , that is
x + 9 - (3x - 2) = 2x + 5 - (x + 9) ← distribute parenthesis on both sides
x + 9 - 3x + 2 = 2x + 5 - x - 9 , simplify both sides
- 2x + 11 = x - 4 ( subtract x from both sides )
- 3x + 11 = - 4 ( subtract 11 from both sides )
- 3x = - 15 ( divide both sides by - 3 )
x = 5
Answer:
i don not know this. but I think
Step-by-step explanation: